Prosedur Sanksi Ekonomi Britania Raya terhadap Rusia: Studi Kasus Konflik Rusia-Ukraina 2022 - Fiksis, Ananda Putra (Global and Policy Journal of International Relations, 2022)
ABSTRACTThe issue of the outbreak of war in Europe, especially the one between Russia and Ukraine in 2022, is one of the conflicts that creates many policies that come from other countries. One of the countries that responded to this conflict was the United Kingdom. The United Kingdom issued a policy of economic sanctions against Russia as an act of defending Ukraine, which has the right to freedom and sovereignty of its country. Based on this fact, the authors are compelled to conduct research on the procedures used by the United Kingdom in implementing its economic sanctions, especially on issues concerning Chelsea Football Club which is owned by a Russian entity. With a period of 2018-2022, this study uses a qualitative descriptive method with secondary data analysis. In this study, the procedure will be dissected through theories of international relations such as the theory of coercive diplomacy by Constantinou, et al. (2016) and the theory of economic sanctions by Filipenko, et al. (2020). The results of this study include, among others, that the United Kingdom provides economic sanctions through several stages, namely the declaration of coercive diplomacy as a policy basis, the use of special laws as the basis for economic sanctions, asset freezing and cessation of forced investment.Keywords: Coercive Diplomacy, Economic Sanctions, United Kingdom, RussiaDOI: https://doi.org/10.33005/jgp.v10i02.3745